A Study of the Bituminous Coal Oxidation Factor in Large Scale Boilers for Estimating GHG Emissions - Seehyung Lee; Jinsu Kim; Jeongwoo Lee; Seung-hee Lee; Seongho Lee; Euichan Jeon (Asian Journal of Atmospheric Environment, 2011)
Korea-specific GHG emissions should be estimated correctly in order to ensure effective measurement of climate change variables. The use of country-specific data that reflects fuel and technology characteristics is needed for accurate GHG emissions estimation. Oxidation factors are used to convert existing data into equivalent GHG emissions, and changes in these oxidation factors are directly related to changes in emissions. As such, the oxidation factor is one of the most important variables in using country-specific data to determine GHG emissions. In this study, the oxidation factor of bituminous coal in large scale boilers was estimated using 4,527 data points sampled from eight large-scale boilers that had been using bituminous coal for two years. The average oxidation factor was determined to be 0.997, which is lower than the oxidation factor of 1 that is recommended by the IPCC G/L for large scale boilers when estimating national GHG emissions. However, an oxidation factor less than 1 is assumed for fluidized bed boilers, internal combustion engines, and other small-scale boilers. Accordingly, studies on oxidation factor estimation should be continued to allow for accurate estimation of GHG emissions.